PENGARUH BCG SCAR TERHADAP HASIL UJ TUBERKULIN ANAK SEKOLAH DASAR (SD) KELAS I-IV (8-13 TAHUN) DI KABUPATEN CILACAP TAHUN 2008 - Sri Nurlaela; Dyah Umiyarni Purnamasari; Dwi Sarwani Sri Rejeki; Erna Kusumawati; Setiyowati Rahardjo (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2009)
Objective research to explore the influence of BCG scar for results of tuberculin test after controlled by covariat variable e.g childrens’s characteristic (age, gender), parents’s characteristic (parents’s education, parents’s occupation) and household size. Method using a case control study held in primary school children attending class I-IV (8-13 years age) in Cilacap district from September–Desember 2008. Sample divided in two group, there are 109 case and 109 control. School children who had result of tuberculin test ≥ 10 mm, respectively, were considered as a case. Control were school children who have result of tuberculin test 0-9 mm, selected by proporsional random sampling. Informations about children’s result of tuberculin test were obtained from secondary datas of tuberculin survey which held on center of Java. Primary datas obtained by interviewing with school children. Result logistic regression demonstrated influence of BCG scar for result pf tuberculin test showed result OR = 0.432, p value = 0,409, it means childrens who had BCG scar had a risk for positive tuberculin 0.432 greater than childrens who had not BCG scar. Based on result, age was confounding variable for influence of BCG scar for results of tuberculin test (OR = 0.434, nilai p = 0.003).